Answer
A 1 3/8
Step-by-step explanation:
Just subtract bro
(2^8 *3^-5* 6^0)^-2 * ((3^-2)/(2^3))^4 * 2^28
anything to the 0 power is 1
(2^8 *3^-5* 1)^-2 * ((3^-2)/(2^3))^4 * 2^28
using the power of power property to take the power inside
(2^(8*-2) *3^(-5* -2) * (3^-2*4)/(2^3*4) * 2^28
simplify
2^ -16 * 3^10 * 3^-8 /2*12 * 2^28
get rid of the division by making the exponent negative
2^-16 * 3^10 * 3^-8 *2*-12 * 2^28
combine exponents with like bases
2^(-16-12+28) * 3^(10-8)
2^(0) *3^2
anything to the 0 power is 1
1*9
9
M < 2 and m < 6 are corresponding angles and are equal....so < 6 = 132.
< 6 and < 8 form a line and are equal to 180
< 6 + < 8 = 180
132 + < 8 = 180
< 8 = 180 - 132
< 8 = 48 <===
Answer:4
Step-by-step explanation:
It’s 4